Evidence for differential acquired drug resistance to anti-tumour necrosis factor agents in rheumatoid arthritis. Issue 6 (8th December 2005) - Finckh, A; Simard, J F; Gabay, C; Guerne, P-A
Abstract : Background: Acquired drug resistance or gradual drug failure has been described with most disease modifying antirheumatic drugs (DMARDs) and is also starting to be recognised with anti-tumour necrosis factor (anti-TNF) agents. Objective: To study acquired drug resistance to anti-TNF agents in rheumatoid arthritis (RA). Methods: Swiss health authorities requested continuous monitoring of patients receiving biological agents. Intensification of co-therapy with traditional DMARDs, gradual dose escalation, and drug discontinuation rates in all patients receiving infliximab, etanercept, or adalimumab, adjusting for potential confounders, were analysed. Intensification of DMARD co-therapy and time to discontinuation of the three anti-TNF agents were analysed using a proportional hazards models. Dose escalation and evolution of RA disease activity (DAS28) were analysed using a longitudinal regression model. Results: 1198 patients contributing 1450 patient-years of anti-TNF treatment met the inclusion criteria. The rate of intensification of traditional DMARD co-therapy over time was significantly higher with infliximab (hazards ratio = 1.73 (99% confidence interval (CI) 1.19 to 2.51)) than with the two other agents. Infliximab also showed significant dose escalation over time, with an average dose increase of +12% (99% CI 8% to 16%) after 1 year, and +18% (99% CI 11% to 25%) after 2 years. No significant differences in discontinuation rates were seen between the three anti-TNF agents (ANOVA, p = 0.67). Evolution of disease activity over time indicated a lower therapeutic response to infliximab (DAS28, p<0.001) compared with etanercept, after 6 months' treatment. Conclusions: In this population, infliximab was associated with a higher risk of requiring intensification of DMARD co-therapy than the other anti-TNF agents and a significant dose escalation over time. Analysis of RA disease activity indicated a reduced therapeutic response to infliximab after the first 6 months of treatment, suggestive of acquired drug resistance.